Sex-related differences in endothelium-dependent vasodilation of human gingiva - János Vág; Tamás László Nagy; Barbara Mikecs (BMC, 2022)
Abstract Background Sex hormones influence circulation, periodontitis, and wound healing. The aim of the study was to compare the endothelium-dependent and independent vasodilation in human gingiva in men and women. Methods Gingival blood flow was evaluated in twelve male and twelve female subjects with healthy gingiva and no systemic conditions after acetylcholine or nitric oxide donor (NitroPOHL). Agonists were administered into the gingival sulcus at the right secondary incisor (test site). Regional gingival blood flow (GBF) was imaged by Laser Speckle Contrast Imager from the marginal gingiva to the mucogingival junction in four consecutive regions (coronal, midway1, midway2 and apical). Blood flow was expressed in Laser Speckle Perfusion Unit (LSPU). The absolute maximal blood flow change (Dmax), the area under the blood flow curve (AUC), and the time to peak (TTP) were calculated. Results Males had higher baseline GBF than females (257 ± 18.2 vs. 225 ± 18.8 LSPU, p < 0.001). Acetylcholine and NitroPOHL significantly increased the GBF in all test regions. The Dmax after the acetylcholine was reduced apically compared to the coronal (90 ± 13 LSPU vs. 117 ± 7 LSPU, p < 0.01), but it was similar after NitroPOHL (78 ± 9 LSPU vs. 86 ± 6 LSPU, p = 0.398) in both sexes. The Dmax and AUC were higher, and the TTP was smaller in men in most regions after acetylcholine but not after NitroPOHL. Conclusion In the human gingiva, the endothelium-independent vasodilation propagates without attenuation in the line of the vascular supply in both sexes. At the same time, the endothelium-dependent ascending vasodilation attenuates similarly in men and women. However, men had more pronounced endothelium-dependent vasodilation than women. Therefore, it might contribute to the increased severity of periodontal disease in men. Trial registration The study was registered with ClinicalTrials.gov on 09.06.2021 (NCT04918563).